If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -2p = 3p + -10 Reorder the terms: 20 + -2p = -10 + 3p Solving 20 + -2p = -10 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 20 + -2p + -3p = -10 + 3p + -3p Combine like terms: -2p + -3p = -5p 20 + -5p = -10 + 3p + -3p Combine like terms: 3p + -3p = 0 20 + -5p = -10 + 0 20 + -5p = -10 Add '-20' to each side of the equation. 20 + -20 + -5p = -10 + -20 Combine like terms: 20 + -20 = 0 0 + -5p = -10 + -20 -5p = -10 + -20 Combine like terms: -10 + -20 = -30 -5p = -30 Divide each side by '-5'. p = 6 Simplifying p = 6
| Y=1+1.50x | | 17/11*5/1=7.272727272727272727272727272727272727272727272727272727272727272727272727272727272727272727272727272727727272727272727272727272 | | 17/11*5/1=7.27272727272727272727272727272727272727272727272727273 | | 17/11*5/1=0 | | Y=18-1.25x | | .875a=42 | | x-8.9=-4.6 | | M-5=10 | | 2-[3-(5-x)]=3x-(8+x) | | 8x+1=12x-3 | | 14-2*6+7= | | -8-5x=2+x | | 8x(5+6)=2 | | 15=b+12 | | 6(6x+10)=-3 | | 3y-1=7 | | 4(x-1)=1 | | 7x(11+7)=-2 | | 5w-6=4 | | 4(x-1)+7=8 | | 7-3(y-2)=19 | | -3e=24 | | 6x+4=9x+10 | | 9+2*8= | | 2y+3x=17 | | 18x-(8x-8)=67 | | -2c+9=19 | | -8x+3=29+2x | | 6(2x+2)=-6 | | 2x^2-5x-20=0 | | 4+8x-3x-1-2= | | 7n-8=3n+4 |